2023
DOI: 10.3390/ijerph20227079
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in E-Cigarette Use and Related Health Effects

Fatima Alam,
Patricia Silveyra

Abstract: Background: Electronic cigarettes (e-cigarettes) comprise a variety of products designed to deliver nicotine, flavorings, and other substances. To date, multiple epidemiological and experimental studies have reported a variety of health issues associated with their use, including respiratory toxicity, exacerbation of respiratory conditions, and behavioral and physiological effects. While some of these effects appear to be sex- and/or gender-related, only a portion of the research has been conducted considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…This has contributed to a notable shift in the United States, particularly among teenagers and young adults, from traditional tobacco cigarettes to various forms of electronic cigarettes [ 2 , 3 ]. While some of these trends have followed sex-specific patterns [ 4 ], the biological and toxicological effects of the various chemicals contained in ENDS in the male and female lung remains poorly understood [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has contributed to a notable shift in the United States, particularly among teenagers and young adults, from traditional tobacco cigarettes to various forms of electronic cigarettes [ 2 , 3 ]. While some of these trends have followed sex-specific patterns [ 4 ], the biological and toxicological effects of the various chemicals contained in ENDS in the male and female lung remains poorly understood [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research has shown that non-phthalate plasticizers can induce endocrine-disrupting effects by engaging mechanisms regulated by NRs [ 15 ]. For these reasons, significant emphasis in current ENDS research has been directed towards scrutinizing the constituents of e-liquids, with a notable gap in the investigation of substances potentially leaching directly from the ENDS devices to the e-liquids, and the specific effects in the male vs. female lung [ 4 ]. In addition, sex-related differences in lung toxicity and diseases have been thoroughly studied and reported across the life span [ 16 ], but research on sex-specific mechanisms of ENDS effects is limited despite reports of sex and gender influences on ENDS toxicity and use [ 4 ].…”
Section: Introductionmentioning
confidence: 99%